Non-steady hydroacoustical problem for a fluid of finite depth - Kubenko, V.D. (Reports of the National Academy of Sciences of Ukraine, 2017)
An analytic solution of a plane problem on the action of a non-steady pressure on the surface of a flat layer of a fluid is constructed. The integral Laplace and Fourier transformations are applied. In the case of a steady region, where a load acts, the inversion of transformations is executed by means of tabular relations and the appropriate theorems of convolution. As a result, the formula for a pressure at an arbitrary point of the fluid is obtained in the closed form. The solution is presented in the form of a sum, whose m-term represents the m-th reflected wave. The retention of a certain number of terms in the solution gives the exact solution of the problem on the given time interval with regard for the necessary number of waves.